2021
DOI: 10.1136/openhrt-2021-001681
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the imaging diagnosis of cardiac disease in Europe

Abstract: ObjectivesWe aimed to explore the impact of the COVID-19 pandemic on cardiac diagnostic testing and practice and to assess its impact in different regions in Europe.MethodsThe online survey organised by the International Atomic Energy Agency Division of Human Health collected information on changes in cardiac imaging procedural volumes between March 2019 and March/April 2020. Data were collected from 909 centres in 108 countries.ResultsCentres in Northern and Southern Europe were more likely to cancel all outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…There are several factors that may explain the decline in cardiac procedures during the pandemic period. The initial interruption of patient referral pathways, such as reduced noninvasive outpatient testing for coronary artery disease during the pandemic, might be partly responsible [18]. It has also been documented that a decrease in acute coronary syndrome hospitalizations occurred, which was partly related to the refusal of patients to go to hospital for fear of contracting SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that may explain the decline in cardiac procedures during the pandemic period. The initial interruption of patient referral pathways, such as reduced noninvasive outpatient testing for coronary artery disease during the pandemic, might be partly responsible [18]. It has also been documented that a decrease in acute coronary syndrome hospitalizations occurred, which was partly related to the refusal of patients to go to hospital for fear of contracting SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…The INCAPS COVID survey was designed to assess the impact of COVID-19 on the use of cardiac imaging during the first lockdown. This survey reported a large reduction (45%-69%) in the total number of procedures in March and April 2020 in European countries[ 98 ]. Although we know that these numbers steadily recovered from Spring 2020, these results raised concern that the underutilization of CVI testing may have disrupted the implementation of primary and secondary strategies for CV disease prevention[ 99 ].…”
Section: Impact On Cardiovascular Imagingmentioning
confidence: 99%
“…Cardiovascular imaging is central to accurate diagnosis of many CVDs. In a survey of 909 centres covering 108 European centres, Williams et al 37 report that total cardiac imaging reduced by 45% in March 2020 and by 69% in April 2020, compared to pre-pandemic levels. The authors demonstrate geographic variation in these trends with greater reductions observed in Southern European nations compared to elsewhere 37 .…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of 909 centres covering 108 European centres, Williams et al 37 report that total cardiac imaging reduced by 45% in March 2020 and by 69% in April 2020, compared to pre-pandemic levels. The authors demonstrate geographic variation in these trends with greater reductions observed in Southern European nations compared to elsewhere 37 . Consistent with these observations, in a study of 52 Italian centres, Dondi et al 38 report reduction in imaging volumes of 67% in March 2020 and 77% in April 2020, compared to the preceding year.…”
Section: Introductionmentioning
confidence: 99%